Process parameter interaction study for mechanical strength of r-HDPE filled calcium carbonate composites - Narayanan, Thinakaran; Abd Razak, Jeefferie (IOP Publishing Ltd, 2024)
The increasing issue of plastic waste disposal has drawn attention to the urgent requirement for sustainable solutions. At the heart of this problem is polyethylene, a crucial industrial resin that has significant implications for recycling. This study aims to explore the feasibility of using recycled highdensity polyethylene (rHDPE) derived from waste carpet as a sustainable alternative material for structural applications that undergo mechanical loads. The primary focus of this research is to incorporate calcium carbonate an easily obtainable and cost-effective inorganic mineral filler into the rHDPE. This will enhance mechanical strength. Calcium carbonate (CaCO3)is widely recognized for their reinforcing properties in various polymer composites, and in addition not only improves the mechanical strength of the blend but also reduces the environmental impact associated with plastic and waste carpet disposal. Our experimental approach involves preparing samples with varying compositions of rHDPE and calcium carbonate. This includes carefully considering extrusion process parameters such as screw speed and melting temperature. Mechanical testing was performed using a universal testing machine following the ASTM standard. The findings of this research are expected to open up new avenues for innovative strategies in reducing plastic waste and promoting the sustainable utilization of waste carpets thereby contributing to the broader field of environmental sustainability.